Beans - International Center for Tropical Agriculture (International Center for Tropical Agriculture, 1987)
The main activities on Phaseolus beans (tissue culture, genotype identification by electrophoresis, and collaborative research) conducted in 1986 by CIAT`s Biotechnology Research Unit are summarized. (CIAT)